Genetic studies revealed differences between European and North American populations of Calypogeia azurea - Buczkowska, Katarzyna; Bączkiewicz, Alina; Gonera, Patrycja (Biodiversity: Research and Conservation, 2016)
Calypogeia azurea, a widespread, subboreal-montane liverwort species, is one of a few representatives of the Calypogeia genus that are characterized by the occurrence of blue oil bodies. The aim of the study was to investigate the genetic variation and population structure of C. azurea originating from different parts of its distribution range (Europe and North America). Plants of C. azurea were compared with C. peruviana, another Calypogeia species with blue oil bodies. In general, 339 gametophytes from 15 populations of C. azurea were examined. Total gene diversity (HT) estimated on the basis of nine isozyme loci of C. azurea at the species level was 0.201. The mean Nei’s genetic distance between European populations was equal to 0.083, whereas the mean genetic distance between populations originating from Europe and North America was 0.413. The analysis of molecular variance (AMOVA) showed that 69% of C. azurea genetic variation was distributed among regions (Europe and North America), 15% - among populations within regions, and 16% - within populations. Our study revealed that C. azurea showed genetic diversity within its geographic distribution. All examined samples classified as C. azurea differed in respect of isozyme patterns from C. peruviana.